Demographics of Pediatric OHCA Survivors With Postdischarge Diseases: A National Population-Based Follow-Up Study - Lee, Tsung-Han; Juan, I-Cheng; Hsu, Hsiu-Ying; Chen, Wen-Liang; Huang, Cheng-Chieh; Yang, Mei-Chueh; Lei, Wei-Yuan; Lin, Chih-Ming; Chou, Chu-Chung; Chang, Chin-Fu; Lin, Yan-Ren (Frontiers in Pediatrics, 2020)
Background: Postdischarge diseases (PDDs) have been reported for adult survivors of out-of-hospital cardiac arrest (OHCA). However, the detailed demographics of pediatric OHCA survivors with PDDs are not well documented, and information regarding functional survivors is particularly limited. We aimed to report detailed information on the PDDs of survivors of traumatic and nontraumatic pediatric OHCA using a national healthcare database. Methods: We retrospectively obtained data from the Taiwan government healthcare database (2011 to 2015). Information on the demographics of traumatic and nontraumatic pediatric OHCA survivors (< 20 years) was obtained and reported. The patients who survived to discharge (survivors) and those classified as functional survivors were followed up for one year for the analysis of newly diagnosed PDDs. The time from discharge to PDD diagnosis was also reported. Results: A total of 2,178 nontraumatic and 288 traumatic OHCA pediatric cases were included. Among the nontraumatic OHCA survivors (n=374, survival rate=17.2%), respiratory tract (n=270, 72.2%), gastrointestinal (n=187, 50.0%) and neurological diseases (n=167, 49.1%) were the three most common PDD categories, and in these three categories, the majority of PDDs were atypical/influenza pneumonia, noninfective acute gastroenteritis and generalized/status epilepsy, respectively. Among the traumatic OHCA survivors (n=21, survival rate=7.3%), respiratory tract diseases (n=17, 81.0%) were the most common, followed by skin or soft tissue (n=14, 66.7%) diseases. Most functional survivors still suffered from neurological and respiratory tract diseases. Most PDDs, except for skin or soft tissue diseases, were newly diagnosed within the first 3 months after discharge. Conclusions: Respiratory tract (pneumonia), neurological (epilepsy), and skin or soft tissue (dermatitis) diseases were very common among both nontraumatic and traumatic OHCA survivors. More importantly, most PDDs, except for skin or soft tissue diseases, were newly diagnosed within the first 3 months after discharge.